EXPERIMENTAL EVALUATION OF THE PROCESS OF ADMINISTRATIVE CULTURE OF FUTURE ECONOMISTS BY MEANS OF MULTIMEDIA TECHNOLOGIES - Homik Oksanа M. (Educological discourse, 2014)
The аrticle deals with the pedagogical research results of the formation process of administrative culture of future economists by means of multimedia technologies; the effectiveness of organizational and pedagogical conditions that favored the formation of administrative culture of future economists by means of multimedia technologies is assessed; evaluation methods of the structural components formation criteria of administrative culture of future economists are presented.